2022
DOI: 10.1186/s12905-022-02128-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of intrauterine antibiotic infusion versus oral antibiotic therapy in the treatment of chronic endometritis in patients during IVF (in vitro fertilization) procedures

Abstract: Background Chronic Endometritis (CE) is a subtle pathology, likely infectious in most cases, with a negative impact on the female fertility, but often overlooked even among fertility specialists. The purpose of the study is to demonstrate the predominant infectious nature of CE and to find the best therapeutic option by comparing the results of oral antibiotic therapy versus intrauterine antibiotic infusion in patients with CE undergoing IVF procedures. The objective was to compare the cure rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Among these, VEGF is important in the vascularization process. By causing the increased expression of molecules that attract stem cells and increased cell migration, PRP treatment can stimulate endometrial receptivity as well as growth [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, VEGF is important in the vascularization process. By causing the increased expression of molecules that attract stem cells and increased cell migration, PRP treatment can stimulate endometrial receptivity as well as growth [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies emphasized that postoperative nausea and vomiting were triggered by hypotension most of the time [12,31,32]. During spinal anesthesia for cesarean section, these problems can be exacerbated by uterine manipulation and peritoneal closure [33]. Some authors advocated that adding an opioid to a local anesthetic in spinal anesthesia would decrease the requirement for intra-operative antiemetic drugs, effects provided mostly by intrathecal fentanyl and not by sufentanyl [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…CD-138, syndecan-1, is a transmembrane heparan sulfate proteoglycan that functions as an extracellular matrix receptor and is a specific marker for plasma cells. In the context of endometrial health and infertility, identifying CD-138+ cells within the endometrial stroma has been correlated with the diagnosis of CE and its potential impact on pregnancy outcomes [ 14 ]. Studies have revealed that CD-138+ cells, particularly in the proliferative-phase endometrium, may be an adverse indicator for pregnancy outcomes in in vitro fertilization (IVF) cycles.…”
Section: Reviewmentioning
confidence: 99%